Inferior Vena Cava Thrombus due to Left Inferior Vena Cava and Ulcerative Colitis - Arai, Hirofumi; Mizukami, Akira; Yoshioka, Kenji; Kuroda, Shunsuke; Iwatsuka, Ryota; Hayashi, Tatsuya; Kimura, Shigeki; Matsumura, Akihiko (TH Open, 2018)
A 29-year-old man with diarrhea and abdominal pain for 2 weeks presented with new-onset left back pain. Contrast-enhanced computed tomography (CT) showed a left inferior vena cava (IVC) crossing over the aorta, and thrombus in the IVC and left renal vein. Colonoscopy and biopsy for assessment of diarrhea and abdominal pain provided a diagnosis of ulcerative colitis. Stasis of blood flow due to left IVC crossing over the aorta, and hypercoagulability due to ulcerative colitis influenced thrombus formation.
Keywords: venous thrombosis; thrombosis; hypercoagulability